试论表决权信托中受益人的权利保护及规制 - Chen Sun (원광법학, 38(3), 2022)
表决权信托是以股权转移为手段旨在集中统一行使表决权的一种特殊的股权信托，其属于公司股东表决权行使方式与信托相结合的产物，是信托机制在公司领域具有实践意义的创造性应用，同时牵涉信托法与公司法上的双重内容。表决权信托理应为受益人的利益最大化而服务，但作为当事人之一的受益人却因其主体身份认定上的单一性，权利与义务的配置处于紊乱状态，始终游离于公司法、证券法等相关法律的规范之外，导致其在信托外部关系中处于特别的优势与劣势地位：既可能遭受目标公司内外部利益相关者的侵害而无法直接主张损害赔偿；也可能恶意利用受托人侵犯其他主体权益却免于遭受责任的追究。 鉴于本土相关规定尚属阙如，本文以衡平理念为指导，学习借鉴域外法中较为成熟的美国公司法中对于表决权信托受益人权利义务体系的构建思路,尝试通过制度层面的创新设计化解难题：即在信托关系设立后依旧由受托人作为目标公司登记股东行使几乎全部的股东权利，但也将例外认可受益人在特定情形下自行主张包括查阅权、股东代表诉讼权、异议股东回购请求权等在内的部分公司股东的权利，以期借力于公司法实现更为全面、有效的受益人权益救济与保障。依据权利与义务相对等的原则，赋予受益人相关保护型权利时也必须防范权利滥用可能引发的风险，兼顾目标公司其他利益相关者合法权益的维护，当于制度层面明确其应承担的一定程度的“股东”义务，以达成其自身权利与义务的统一，并且实现其与目标公司利益相关者、公共利益间的利益平衡。同时，基于受益人属于单纯利益享有者的信托法定位以及表决权信托设立私密性的考虑，将受益人需要承担的义务内容主要确定为信息披露义务，将约束对象限定为设立于上市公司中且信托股权达到相当比例的表决权信托受益人。 A voting trust is a special kind of equity trust that aims to centralise and unify the exercise of voting rights by means of equity transfer. It is a product of the combination of the exercise of voting rights by shareholders of a company and a trust, and is a creative application of the trust mechanism in the field of companies with practical significance, involving both trust law and company law. The voting rights trust is supposed to serve the interests of the beneficiaries, but the beneficiaries, as one of the parties, are in a state of disorder due to the single identity of their subject, and the configuration of their rights and obligations is always outside the regulation of the company law, securities law and other relevant laws, resulting in their special advantages and disadvantages in the external relations of the trust: they may be infringed by the internal and external stakeholders of the target company, and are unable to claim damages directly. They may not be able to claim damages directly against those with an interest in the target company, or they may be able to use the trustee in bad faith to infringe on the rights and interests of other parties without being held liable. In view of the lack of relevant local regulations, this article takes the concept of equity as a guide, and learns from the more mature US corporate law on the construction of the rights and obligations of beneficiaries of voting rights trusts, and attempts to solve the problem through an innovative design at the institutional level: that is, after the establishment of the trust relationship, the trustee will continue to exercise almost all of the shareholders' rights as the registered shareholder of the target company, but will also exceptionally allow the beneficiaries to The trustee will continue to be the registered shareholder of the target company after the establishment of the trust relationship, but will also exceptionally allow the beneficiaries to claim some of the rights of shareholders, including the right of access, the right of representative action and the right of repurchase by dissenting shareholders, under certain circumstances, in order to achieve more comprehensive and effective remedies and protection of the beneficiaries' rights and interests through the company law. In accordance with the principle of equality of rights and obligations, when granting beneficiaries relevant protective rights, it is also necessary to prevent the risk of abuse of rights and to take into account the protection of the legitimate rights and interests of other stakeholders of the target company, and to clarify at the institutional level the degree of "shareholder" obligations they should undertake, so as to achieve the unity of their rights and obligations. It is also important to strike a balance between the interests of the beneficiaries, the stakeholders of the target company and the public interest. At the same time, based on the trust law's position that beneficiaries are mere beneficiaries and the private nature of the establishment of voting rights trusts, the obligations of beneficiaries are mainly defined as information disclosure obligations, and the target group is limited to beneficiaries of voting rights trusts that are established in listed companies and have a significant proportion of the trust's shareholding. KCI Citation Count: 0